The Extraordinary Complaint in the Polish Legal System. Selected Remarks on the Admissibility of the Extraordinary Complaint in Bankruptcy Proceedings - Panek, Bartłomiej (Przegląd Prawniczy Uniwersytetu im. Adam Mickiewicza, 2024)
This article analyses the possibility of utilizing the institution of an extraordinary complaint, which constitutes one of the extraordinary means of appeal in the Polish legal system, as a legal tool available to individuals inbankruptcy proceedings. The article also indicates that an extraordinary complaint, when examined from a systemic perspective within the Polish legal order - particularly in light of the judgment of the European Court of Human Rights in Strasbourg in Wałęsa v. Poland - is a measure that raises certain legal concerns and prompts some political controversies. However, in the author’s opinion, this does not contradict the fact that, regardless of the emerging doubts and controversies (and irrespective of potential future legislative changes regarding this institution), such a measure is extremely important from the perspective of individuals (as subjects of freedoms and rights derived from such conventions as the Constitution of the Republic of Poland and the Convention for the Protection of Human Rights and Fundamental Freedoms, including the right to a fair trial). State authorities should make every possible effort to ensure that this measure is fully effective, efficient, and accessible to individuals at the relevant moment - both in theory and in practice. The article aims to determine whether and to what extent an extraordinary complaint may be applied in bankruptcy proceedings, where the primary objective is to satisfy creditors and organize the debtor’s obligations. At the same time, considering the postulate of ensuring the full effectiveness and efficiency of this means of appeal available to individuals, the author also seeks to examine whether such a measure can be applied in bankruptcy cases that concern the sale of an enterprise under a pre-pack procedure. The article highlights that, despite the formal possibility of filing extraordinary complaints in bankruptcy proceedings, in practice, public authorities do not make use of this measure in relation to rulings issued during bankruptcy proceedings. The article emphasizes how the lack of such action contradicts the constitutional principles of a modern democratic state (including the principle of a democratic state governed by the rule of law that implements the principles of social justice, as indicated in Article 2 of the Constitution of the Republic of Poland, as well as the resulting principle of protecting citizens’ trust in the state and its legal system). An extraordinary complaint should be a fully effective and efficient remedy, also within bankruptcy proceedings. The conclusions indicate that an extraordinary complaint in bankruptcy proceedings should also be admissible in situations where the bankrupt’s assets are sold (including cases of enterprises sold under the pre-pack procedure), particularly when such actions may lead to violations of the constitutional freedoms and rights of individuals (both creditors and the debtor). In the author’s opinion, the possibility of filing such a complaint should be analysed on a case by-case basis, taking into account the legal consequences of decisions made in the course of the liquidation of bankruptcy assets.